Digital rhetoric on Twitter: an analysis of President Lenín Moreno’s tweet in 2019.: Digital rhetoric on Twitter: an analysis of President Lenín Moreno’s tweet in 2019 - Ynciarte, Luis Eduardo (Quórum Académico, 2023)
This research presents an analysis of Lenín Moreno speech through the social network Twitter in 2019. The methodological strategy used for development is the critical analysis of discourse from two levels: the first level, it guides the analysis of resources through semantic domains: attitude, gradation and commitment in the discourse; and, the second level, the interpretation of the discursive positions, narrative configurations and semantic spaces. The investigation allows to verify the idea about the incidence of the speeches, the language and the texts that disseminate the voices of power captured by the public. It is concluded that the use of Twitter can reach the media logic where the social imaginary of the differences between them and us crystallizes by framing the news withnegative aspects.